The effect of implementing parenteral nutrition guideline on growth and clinical outcomes in preterm infants: a comparative study - Majid Mahallei; Lida Gorbani; Mohammad Bagher Hoseini; Elnaz Shaseb; Bahareh Mehramuz; Khatereh Rezazadeh (BMC Pediatrics)
Abstract Background To improve the nutritional management of premature infants in neonatal intensive care units (NICUs), we developed and implemented a standardized parenteral nutrition (PN) protocol aimed at optimizing early macronutrient delivery. This study evaluated the impact of the new protocol on growth parameters and clinical outcomes in preterm neonates. Methods This prospective, non-randomized interventional cohort study included two groups of preterm infants born before 32 weeks of gestation or with birth weights under 1250 g. The PRE group received individualized PN formulations based on clinician discretion, while the POST group received PN guided by a newly introduced, stepwise algorithmic protocol aiming to optimize early protein and energy intake. Anthropometric data, daily energy and macronutrient intakes during the first 14 days, and weight at day 28 were collected. Clinical outcomes—including the incidence of sepsis, necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH) retinopathy of prematurity (ROP) and hospitalization duration—were compared between groups. Results A total of 139 infants were enrolled (69 PRE, 70 POST). While weight gain in the first 14 days was similar, the POST group showed significantly greater weight and weight velocity by day 28. These improvements paralleled higher mean daily energy and protein intakes during the early postnatal period. The incidence of bacterial sepsis was significantly reduced in the POST cohort, possibly reflecting better nutritional status and improved PN preparation practices. Although other complications did not differ significantly, fewer infants in the POST group required prolonged hospitalization (> 90 days). Conclusion Implementation of a standardized PN protocol improved early nutritional intake and was associated with better growth and reduced infection rates in premature infants. These findings support the use of structured PN strategies to enhance early neonatal outcomes in NICU settings. Trial registration The Iranian Registry of Clinical Trials (http//www.irct.ir) with the identification No. IRCT20240519061838N2. Registered 24 November 2024.